Issue Information TOC. Issue 1 (12th December 2019) - Unknown
Abstract : Cover : In Santamaría et al. (https://doi.org/10.1002/cptx.89 ), the image shows (A ) The whole ovary was serially sectioned (5 µm thick) and 1 out of every 10 sections was stained with picrosirius‐hematoxylin (P‐H) for morphological observation. Magnification: (B ) 100×, (C ) and (D ) 400×. Red circles represent oocytes belonging to nests. Pink arrow represents primary follicle; blue arrow, early primary follicle; and green arrow, primordial follicle.